2015
DOI: 10.1517/14740338.2015.1034105
|View full text |Cite
|
Sign up to set email alerts
|

Short-term impacts of sodium/glucose co-transporter 2 inhibitors in Japanese clinical practice: considerations for their appropriate use to avoid serious adverse events

Abstract: Sodium/glucose co-transporter 2 inhibitors (SGLT2i) represent a novel class of glucose-lowering agents that lower plasma glucose levels through pharmacological inhibition of glucose reuptake from the kidney, independent of insulin secretion and action. Clinical trials of SGLT2i demonstrated therapeutic benefits on glycemic control and bodyweight in individuals with type 2 diabetes, with few cases of serious adverse events (SAEs). However, a considerable number of SAEs were reported in patients receiving SGLT2i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 14 publications
3
86
3
1
Order By: Relevance
“…The safety of SGLT2 inhibitors in Japanese patients with T2DM has emerged as an important issue owing to the high incidence of serious AEs, especially urogenital infections, hypoglycemia, dehydration, and skin complications, that were reported in the first 3 months of using ipragliflozin or other SGLT2 inhibitors [11]. Here, we report the final results of a PMS, which was conducted to investigate the safety of ipragliflozin administered for up to 1 year in elderly Japanese patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The safety of SGLT2 inhibitors in Japanese patients with T2DM has emerged as an important issue owing to the high incidence of serious AEs, especially urogenital infections, hypoglycemia, dehydration, and skin complications, that were reported in the first 3 months of using ipragliflozin or other SGLT2 inhibitors [11]. Here, we report the final results of a PMS, which was conducted to investigate the safety of ipragliflozin administered for up to 1 year in elderly Japanese patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported the results of an interim analysis (STELLA-ELDER [10]) that was conducted in order to address possible safety concerns regarding SGLT2 inhibitors in realworld clinical practice in Japan, where a large number of serious adverse events (AEs) were reported in the first 3 months of using these drugs [11]. The PMS registered 8687 patients across 2634 institutions, and 6-month data were available for up to 7170 patients, while 1-year data were available for up to 1140 patients [10].…”
Section: Introductionmentioning
confidence: 99%
“…These cases of DKA were not typical because patients had nearly normal blood glucose levels and showed few symptoms. Furthermore, a recent meta-analysis of clinical trial data demonstrated an increased risk of ketoacidosis with SGLT2 inhibitor treatment in patients with type 2 diabetes (26). A separate analysis based on data from 17,596 patients reported a low frequency (,0.1%) of serious DKA events across treatment groups in the canagliflozin type 2 diabetes clinical trial program (27).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that SGLT2i induces hyperglucagonemia to compensate for the SGLT2i-mediated glucosuria. Elevated glucagon enhances proteolysis that contributes to reduction of fat mass, release of free fatty acids (FFAs) from the adipose tissue which might results in euDKA [5].…”
Section: Potential Mechanisms Of Sglt2i-induced Eudkamentioning
confidence: 99%
“…This process cause decrease in plasma glucose pool, which initiates the process of gluconeogenesis and FFAs from liver. This may lead to release of ketone bodies and euDKA when patients are on SGLT2i therapy for the treatment of T2D [1,4,5].…”
Section: Potential Mechanisms Of Sglt2i-induced Eudkamentioning
confidence: 99%